The heritage of light and shade in Cairo - Hossam Mahdy (Ochrona Dziedzictwa Kulturowego, 2025)
Conservation principles and practices were introduced to Islamic historic cities by European orientalists in the late nineteenth century and early twentieth century. While they played an important role in the conservation of the historic built heritage, they paid little or no attention to some intangible aspects of that heritage. The place of light and shade in the city is one of these missed aspects in practices of conservation in Islamic historic cities up to the present. Perhaps this was caused by the difference in symbolic meanings and significance of light and shade between Western and Islamic worldviews.